A comparison of manual therapy and extracorporeal shockwave therapy in patients with carpal tunnel syndrome - Torun, Neslihan; Tuncer, Aysenur (TURKEY ASSOC PHYSIOTHERAPISTS)
Purpose: To investigate the effects on pain, symptom severity, and functionality of different physiotherapy methods applied to patients with carpal tunnel syndrome and to evaluate the advantages of these over each other.Methods: A total of 75 patients (69 females, 6 males) aged 25-60 years were separated into 3 groups. The patients in Group 1 were given a home exercise program (HP), including median nerve and tendon gliding exercises. Group 2 received the same HP plus manual therapy (MT), including soft tissue and joint mobilisation. Group 3 received the same HP plus extracorporeal shockwave therapy (ESWT). Pain severity was evaluated with a Visual Analog Scale. Symptom severity and levels of functionality were evaluated with the Boston Carpal Tunnel Syndrome Questionnaire and the Cochin Hand Function Questionnaire. All the patients were evaluated before and after treatment.Results: While there was a significant decrease in the resting and activity pain levels of each 3 groups after the treatment (p<0,05), no significant difference was found between MT and ESWT groups (p> 0.05). However, the pain values of these two groups were significantly decreased compared to the EP group (p <0.05). The pain values of both groups were significantly lower than those of the HP control group (p <0.05). A statistically significant increase was determined in the level of functionality in all the groups after treatment (p<0.05). The decrease in symptom severity and the increase in functionality were significantly greater in the MT and ESWT groups compared to the HP group (p<0.05). After the treatment, there were no superiorities with respect to the pain, symptom severity, and functionality values of the MT and ESWT groups (p>0.05).Conclusion: In our study, the MT and ESWT applications we used in patients with CTS patients provided significant improvement compared to HP exercises only. We speculate that some differences that are not seen in the early period can be seen in long-term follow-up. Further studies should be performed to assess the long-term results.
Keywords: Extracorporeal Shockwave Therapy; Manual Therapy; Tendon Gliding; Nerve Gliding; Carpal Tunnel Syndrome